Autonomous Orientation and Delinquent Behavioral Change : A Case Study of Ex-Juvenile Entrepreneurs in Katsina State, Nigeria - Usman, Bilyaminu; Sharizal, Hashim (Human Resource Management Academic Research Society, 2020)
Contemporary Entrepreneurship discussion revealed the importance and the positive influence of autonomous orientation as one of the Entrepreneurial orientations (EO) towards organization performance and profitability. However, discussion of autonomous in the context of individuals such as entrepreneur behavioral change impact still silent, especially in the context of ex-juvenile entrepreneurs that can give an understanding into the Entrepreneurship body of knowledge. Therefore, the purposes of the research are to understand the role of autonomous orientation as one of the Individual Entrepreneurial Orientations (IEO) towards the delinquent behavioral change of ex-juvenile entrepreneurs. The study employed qualitative methods and in-depth interview to 10 research informants of ex-juvenile entrepreneurs that operate entrepreneurial activities in Katsina state, Nigeria. The study used thematic and NVivo 12 Pro to organize and analyze the data. The study found that ex-juvenile entrepreneurs are autonomous and more importantly autonomous orientation has a positive influence on ex-juvenile entrepreneurs’ delinquent behavioral change. This finding provides a fresh knowledge about the IEO potential in the entrepreneur self-development and insight into the entrepreneurship policymakers.